Daniel Gviliemvs Trillervs, Phil. et Med. D. Consiliarius Aulicus, Regis Pol. Elect. Sax. item Leucopetr. et Archiater Primarius. nat. Erfurti d. 10. Febr. 1695 - Lippold, Franz (1747)
Deutscher Arzt und Schriftsteller